Ir(IV) Sulfoxide-Pincer Complexes by Three-Electron Oxidative Additions of Br-2 and I-2. Unprecedented Trap-Free Reductive Elimination of I-2 from a formal d(5) Metal - Frieß, Sibylle; Benyak, Anna; Herrera, Alberto Cesar; Escalona Bauza, Ana Melissa; Heinemann, Frank Wilhelm; Langer, Jens; Fehn, Dominik; Pividori, Daniel Maximilian; Grasruck, Alexander; Munz, Dominik; Meyer, Karsten; Dorta, Romano (Inorganic Chemistry, 2022)
Oxidative addition of 1.5 equiv of bromine or iodine to a Ir(I) sulfoxide pincer complex affords the corresponding Ir(IV) tris-bromido or tris-iodido complexes, respectively. The unprecedented trap-free reductive elimination of iodine from the Ir(IV)-iodido complex is induced by coordination of ligands or donor solvents. In the case of added I-, the isostructural tris-iodo Ir(III)-ate complex is quickly generated, which then can be readily reoxidized to the Ir(IV)-iodido complex with FcPF(6) or electrochemically. DFT calculations indicate an "inverted ligand field" in the Ir(IV) complexes and favor dinuclear pathways for the reductive elimination of iodine from the formal metal center.
CRIS-Team WoS Importer:2022-01-21